Cultures in Dialogue. Institutional and Individual Challenges for EU Institutions and EU Citizens from the Perspective of Legal Linguistics - Luttermann, Karin (HERMES - Journal of Language and Communication in Business, 2011)
In the European Union, numerous cultures have entered into dialogue. Currently, there are 23 ofﬁcial languages (EU languages) and therefore 506 possible language combinations for translation. This makes demands on the EU institutions and on EU citizens as well. Linguistic divergence makes legal certainty a rather shaky matter. There are also divergences from the EU linguistic regime regarding the ofﬁcial and the working languages. For reasons of efﬁciency, the institutions of the Union communicate internally in merely a small number of working languages, for the most part without any basis for this in the Rules of Procedure. The Court of Justice of the European Union traditionally uses French. All documents are translated from the language of the case into the working language. Although the decision, formulated in French, is re-translated into the language of the case, this translated version is classiﬁed as the original version and not as a translation. This is of importance for the status of authenticity because the decision only has full legal effect in the language of the case. Traditional language models favour a reduction of the EU languages. Their representatives argue either with regard to the practice of the use of three languages in the EU institutions, or they advocate English as a global language, or they call for neutral languages. In contrast, the European Reference Language Model, which is developed along the lines of legal linguistics, suggests a concept of reference and native languages. It would lead to a reduction in the translation load in Brussels and Luxembourg. But ﬁrst and foremost, it would be able to improve the linguistic quality of legal documents (e.g., directives, regulations) and therefore also their application to legal practice (e.g. legal certainty, comprehensibility of legal texts). At the same time, the model respects the dignity of each EU Member State in the form of its language.